2013
DOI: 10.1371/journal.pone.0067251
|View full text |Cite
|
Sign up to set email alerts
|

PCSK6 VNTR Polymorphism Is Associated with Degree of Handedness but Not Direction of Handedness

Abstract: Although the left and right human cerebral hemispheres differ both functionally and anatomically, the mechanisms that underlie the establishment of these hemispheric specializations, as well as their physiological and behavioral implications, remain largely unknown. Since cerebral asymmetry is strongly correlated with handedness, and handedness is assumed to be influenced by a number of genetic and environmental factors, we performed an association study of LRRTM1 rs6733871 and a number of polymorphisms in PCS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 28 publications
0
74
0
Order By: Relevance
“…Statistically significant differences between activity in the left versus right hemisphere are indicated by an asterisk. seem to be subject to imprinting and may be linked to the degree rather than direction of handedness 128 . PCSK6 encodes a protease enzyme that cleaves Nodal, a protein that has a role in the regulation of the left-right visceral axis (of the heart, lungs, and so on) in early embryogenesis 127 .…”
Section: Genetics Of Brain Lateralizationmentioning
confidence: 99%
“…Statistically significant differences between activity in the left versus right hemisphere are indicated by an asterisk. seem to be subject to imprinting and may be linked to the degree rather than direction of handedness 128 . PCSK6 encodes a protease enzyme that cleaves Nodal, a protein that has a role in the regulation of the left-right visceral axis (of the heart, lungs, and so on) in early embryogenesis 127 .…”
Section: Genetics Of Brain Lateralizationmentioning
confidence: 99%
“…We calculated the following laterality index: ((sum of right hand crosses -sum of left hand crosses) / sum of all crosses) *100. Thus, scores ranged from -100 to 100 with negative values indicating a left hand preference and positive values a right hand preference (including zero) (Arning et al, 2013;Nicholls, Thomas, Loetscher, & Grimshaw, 2013). Based on the laterality index, participants were allocated to one of the following groups: left-handers (LI's between -100 and -50), mixed-handers (LI's between -50 to 50), and right-handers (LI's between 50 to 100).…”
Section: Edinburgh Handedness Inventory the Edinburgh Handedness Invmentioning
confidence: 99%
“…Thus, most authors today agree that handedness is likely to be a multifactorial trait that is determined by several different genetic and non-genetic factors (e.g., [5][6][7][8]). A number of contributing loci have been identified by GWAS and candidate gene studies using handedness questionnaires or hand skill tests like the pegboard test as phenotypes, e.g., LRRTM1, PCSK6 and AR [9][10][11][12][13][14][15]. However, the general understanding is that there is likely a large number of yet unidentified genetic contributions to handedness [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is commonly measured as a continuous variable using a lateralization quotient (LQ) [18], ranging from −100 (consistent left-handedness) to +100 (consistent right-handedness). Interestingly, findings from a recent PCSK6 candidate gene study on handedness showed that the direction and degree of handedness might underlie differential genetic influences [9]. Thus, using the LQ as a phenotype instead of differentiating between left-and right-handers could potentially yield interesting insights into the genetics of handedness.…”
Section: Introductionmentioning
confidence: 99%